The Relationship of Achievement Motivation and Cognitive Style with Concrete Construction Learning Outcomes - Santosa , Teguh; Oktaviany, Venny (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Purpose - This research is to determine the relationship of achievement motivation and cognitive style with concrete construction learning. Methodology/approach - It was a quantitative research with a correlation analysis method. The samples were students of the Faculty of Engineering, Civil Engineering Program, Semester V at the University in Bekasi - West Java amounted to 18 students selected by proportional random sampling. The data were analyzed with inferential statistics using regression and correlation analysis. Findings - The results concluded that (1) there is a positive correlation between achievement motivation with concrete construction learning; (2) there is a positive correlation between cognitive style with concrete construction learning; (3) there is a positive correlation between achievement motivation and cognitive style together have positive with concrete construction learning. Novelty/value- Novelty/Values ​​of this research are designers and managers of learning concrete construction courses can create a learning process by continuously growing achievement motivation and cognitive style in students and the need for a consistent attitude in their implementation as